Financial Incentives for Covid-19 Vaccines in a Rural Low-Resource Setting: A Cluster-Randomized Trial - Mayol-Miranda, A (Nature Research, 2023)
We implemented a clustered randomized controlled trial with 6,963 residents in six rural Ghana districts to estimate the causal impact of financial incentives on coronavirus disease 2019 (COVID-19) vaccination uptake. Villages randomly received one of four video treatment arms: a placebo, a standard health message, a high cash incentive (60 Ghana cedis) and a low cash incentive (20 Ghana cedis). For the first co-primary outcome—COVID-19 vaccination intentions—non-vaccinated participants assigned to the cash incentive treatments had an average rate of 81% (1,733 of 2,168) compared to 71% (1,895 of 2,669) for those in the placebo treatment arm. For the other co-primary outcome of self-reported vaccinations 2 months after the initial intervention, the average rate for participants in the cash treatment was 3.5% higher than for participants in the placebo treatment (95% confidence interval (CI): 0.001, 6.9; P = 0.045): 40% (602 of 1,486) versus 36.3% (672 of 1,850). We also verified vaccination status of participants: in the cash treatment arm, 36.6% (355 of 1,058) of verified participants had at least one dose of the COVID-19 vaccine compared to 30.3% (439 of 1,544) for those in the placebo—a difference of 6.3% (95% CI: 2.4, 10.2; P = 0.001). For the intention and the vaccination outcomes, the low cash incentive (20 Ghana cedis) had a larger positive effect on COVID-19 vaccine uptake than the high cash incentive (60 Ghana cedis). Trial identifier: AEARCTR-0008775 . © 2023, The Author(s).